(untitled) (World Bulletin of Public Health, 2022)
New tetradentate ligand (BHAP)(5-bromopyridin-2-yl)imino)ethyl)-2-hydroxy -5-methyl phenyl)azo)-1-phenyl-2,4-dihydro-3N-pyrazol-3-one was prepard by the reaction of 3-amino-1-phenyl-2-pyrazolin -5-one and 2-hydroxy-5- methylaceto phenone to form azo compound,then this compound react s with 2-amino -5-bromopyridine to required (BHAP)ligand. Series of mononuclear complexes of (BHAP) ligand were prepared with Mn(II), Co(II), Zn(II), Cd(II), Ag(I), Pd(II) ions, which have a general formula [M(BHAP)ClH2O]. nH2O for Mn(II), Co(II), Zn(II), Cd(II), Pd(II), complexes (n=1,2,3...) while the complexes of other ions have ageneral formulas [Ag(BHAP)], and [Pd(BHAP)]Cl .The synthezid ligand and it`s complexes were charaterized by (mass, (1H,13C-NMR), Element analysis, FT-IR, UV-Vis, Molar condictivity, solubility, Magnetic susceptibility, melting point,and (TLC), form the results that obtained from previous measurments tetrahedral geometry of Ag(I) complex, square planer of Pd(II) complexe, and octahedral geometry for the complexes of other ions were proposed. Stability constants of the complexes were calculated at (25)0C by using Mole Ratio method, their data agreed with Irving –Williams series as the following sequence for octahedral divalent metal ions of the first series:Mn(II) < Co(II) < Zn(II). Also the preperd complexes showed high stability with time, and good inhiption activity against two types of pathogenic bacteria (Staphylococcus aureus, and Escherich ia coli).